Edible flowers of ornamental plants: a food promise in the sustainability sector - Pinto, Sara (2017)
The growing interest in nutraceutical ingredients and functional foods has increased research into new foods that provide beneficial health. Although flowers were already used as food in ancient times, they have only recently sparked off nutraceutical research focusing on new agronomic and economic horizons, which are part of the concept of sustainability. OBJECTIVES: Having in mind the potential of edible flowers as source of bioactive compounds and related antioxidant activity, this work evaluated the contents of total phenolics and flavonoids, in aqueous extracts of rose (Rosa canina L.), marigold (Calendula officinalis L.) and camellia (Camellia L.). Additionally, the antioxidant activity of all the extracts was evaluated.